OPTIMASI HASIL PRODUKSI GENTENG MENGGUNAKAN GOAL PROGRAMMING SEBAGAI MONOGRAF - Nisa, Choirotun; Setiawan, Susi; Fatahillah, Arif (Kadikma, 2019)
Optimization is the best decision making activity that can be carried out by the company related to the industry in question within existing limitations by involving limiting determinant variables. The problems faced by UD Pastijaya are the limitations that exist in an effort to maximize the production of roof tiles by optimally using the variable variables available to obtain an increase in tile production. The solution that can be done is to use the Goal Programming method which is the development of the Linear programming method. This method is used to solve the problem of determining the amount of optimal production with limited resources as targets to be achieved. The optimization results are carried out by using the POM-QM assistance application. The number of tile production has increased in several types of tiles including coral reefs as many as 52425 units, press as many as 51955 units, morando as many as 12441 units, and wuwung as many as 9310 units. Keywords: Production optimization, tile, Goal Programming